Perceptions of COVID-19 vaccine among different adult age group populations in Northern Uganda: a cross-sectional study - David L Kitara; Steven Baguma; Christopher Okot; Denis Acullu; Denis Ochula; Pamela A Okot; Patrick O Odong; Smart G Okot; Francis P Pebolo; Freddy W Drinkwater Oyat; Eric N Ikoona; Nelson O Alema; et al. (Inishmore Laser Scientific Publishing Ltd, 2023)
# Background At the time when COVID-19 was declared a pandemic in March 2020, its spread in the African continent was slow. However, confirmed cases of the virus have since risen steadily over the years in the African continent for many reasons. This study aimed to determine factors associated with perceptions of COVID-19 vaccines among adult age-group populations in northern Uganda. # Methods We conducted this study as part of a larger study to determine factors associated with COVID-19 vaccine hesitancy/acceptance among 723 adult age-group populations selected by stratified and systematic sampling approaches from northern Uganda. We used a questionnaire with an internal validity of Cronbach's α= 0.772. A five-point Likert scale, with responses categorized as strongly agree "SA", agree "A", neutral "N", disagree "DA", and strongly disagree "SD", was used to assess participants' perceptions on COVID-19 vaccines. A multivariable regression analysis was conducted with P-value set at <0.05. # Results Overall, 723 participated in the study with a mean age of 31.4 years (standard deviation, SD, +10.1). The majority 54.5% (n=394) were males. There were no significant differences in perceptions of COVID-19 vaccines among age-group populations (adjusted odds ratio, aOR=0.99, 95% confidence interval, CI=0.98-1.01). Key finding include: (i) it was important to take a COVID-19 vaccine (aOR=1.02, 95% CI=1.00-1.04); (ii) vaccines have unlikely unforeseen side effects (aOR=0.98, 95% CI=0.97-0.99); (iii) vaccines were unlikely being promoted for commercial gains (aOR=0.98, 95% CI=0.97-0.99); and children could take COVID-19 vaccines (aOR=1.02, 95% CI=1.00-1.03). Stratified by age-groups, the 20-29-year-old perceived COVID-19 vaccines developed in Uganda as unlikely safe and effective (aOR=0.59, 95% CI=0.35-0.97), and COVID-19 vaccines have likely unforeseen side-effects (aOR=2.1, 95% CI=1.3-3.6). While the ≥50-year-old group perceived that COVID-19 vaccines were unlikely being promoted for commercial gains (aOR=0.2, 95% CI=0.1-0.6). # Conclusions There were no substantial differences in perceptions on COVID-19 vaccines in adult age-group populations in northern Uganda. The determinants of COVID-19 vaccine perceptions were its importance against the virus; vaccines have unlikely unforeseen side-effects, and children could take it. Stratified by age-groups, some age-groups perceived COVID-19 vaccines developed in Uganda as unlikely safe and unlikely being promoted for commercial gains.